Primary Extraskeletal Myxoid Chondrosarcoma: A Case Report - Renuka Bangalore Nagaraj (JCDR Research and Publications Private Limited, 2021)
Extraskeletal Myxoid Chondrosarcoma (EMC) is a rare malignant soft tissue sarcoma with uncertain differentiation, most often seen in males. The incidence is 3% of all soft tissue tumours with limited literature available on its cytological features. EMC may arise from lower extremities, upper extremities, retroperitoneum, pelvis, and buttocks. This case report was an effort to understand the role of Fine Needle Aspiration Cytology (FNAC), histopathology and immunochemistry in the diagnosis of EMC. Authors hereby report a case of a 70-year-old male patient with slow-growing soft tissue swelling on the back just behind the right shoulder who was referred for FNAC. Patient complete history and clinical findings were recorded. Radiological images were suggestive of malignant soft tissue neoplasm with no involvement of underlining bone. FNAC reveled tumour cells which appeared monotonous and they were seen in a myxoid stroma background. Subsequently, the excised lesion was sent for histopathological examination and the report revealed the presence of abundant chondromyxoid matrix material within which were found numerous elongated spindly shaped cells. These cells had moderately pleomorphic elongated nuclei with focal solid fibrocollagenous areas along intersecting fascicles of the moderately pleomorphic spindly cell. Few of these cells had multilobulated bizarre nuclei with nuclear inclusions. Immunohistochemical stains showed diffuse positivity for S-100, vimentin, and focally positive for Epithelial Membrane Antigen (EMA). The FNAC, histopathology and immunohistochemical features confirm the diagnosis of EMC on right shoulder. It’s a rare tumour whose diagnosis is made depending on history, clinical location, growth pattern, histopathology, and immunohistochemistry.